Isolation and Structures of 1, 2, 3‐Triazole‐Derived Mesoionic Biscarbenes with Bulky Aromatic Groups. Issue 9 (2nd March 2016) - Iwasaki, Haruka; Yamada, Yuji; Ishikawa, Ryuta; Koga, Yuji; Matsubara, Kouki
Abstract: 1, 2, 3‐Triazole‐derived mesoionic biscarbenes bridged by a pyridylene group were synthesized and their structures were determined. Bulky substituents on the carbene rings stabilized the carbenes, which enabled their crystal structures to be determined. As implied by DFT calculations and the experimental results, the carbenes are partly reduced to anionic radical species in the presence of strong bases. This suggests that the pyridylene and triazolylidene moieties endow molecules with both electron‐acceptor and ‐donor properties. A rare example of an iron complex with a pincer carbene was synthesized. Abstract : 1, 2, 3‐Triazole‐derived mesoionic biscarbenes bridged by a pyridylene group are synthesized and characterized. The carbenes are thought to be partly reduced to anionic radical species in the presence of strong bases, which suggests that these moieties endow molecules with both electron‐acceptor and ‐donor properties. A rare example of an iron complex with a pincer carbene is synthesized.